Phenolics from medicinal and aromatic plants: characterisation and potential as biostimulants and bioprotectants - Kisiriko, Musa; Anastasiadi, Maria; Terry, Leon A.; Yasri, Abdelaziz; Beale, Michael Henry; Ward, Jane Louise (MDPI, 2021)
Biostimulants and bioprotectants are derived from natural sources and can enhance crop growth and protect crops from pests and pathogens, respectively. They have attracted much attention in the past few decades and contribute to a more sustainable and eco-friendly agricultural system. Despite not having been explored extensively, plant extracts and their component secondary metabolites, including phenolic compounds have been shown to have biostimulant effects on plants, including enhancement of growth attributes and yield, as well as bioprotectant effects, including antimicrobial, insecticidal, herbicidal and nematicidal effects. Medicinal and aromatic plants are widely distributed all over the world and are abundant sources of phenolic compounds. This paper reviews the characterisation of phenolic compounds and extracts from medicinal and aromatic plants, including a brief overview of their extraction, phytochemical screening and methods of analysis. The second part of the review highlights the potential for use of phenolic compounds and extracts as biostimulants and bioprotectants in agriculture as well as some of the challenges related to their use.
Keywords: biostimulant; bioprotectant; phenolic; phenolic; medicinal; aromatic